#### Answer

33

#### Work Step by Step

$(f-g)(x)=f(x)-g(x)$
$(f-g)(x)=f(x)-g(x)=x^2-3x+8-(-2x-5)=x^2-x+13$
Plug in $x=5$ into $(f-g)(x)$: $(f-g)(5)=(5)^2-5+13=25-5+13=33$

Chegg costs money, GradeSaver solutions are free!

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

33

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.